2022
DOI: 10.3390/s22134895
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Secure and Scalable Maritime Monitoring System Using Blockchain and Low-Cost IoT Technology

Abstract: Maritime Domain Awareness (MDA) is a strategic field of study that seeks to provide a coastal country with an effective monitoring of its maritime resources and its Exclusive Economic Zone (EEZ). In this scope, a Maritime Monitoring System (MMS) aims to leverage active surveillance of military and non-military activities at sea using sensing devices such as radars, optronics, automatic Identification Systems (AISs), and IoT, among others. However, deploying a nation-scale MMS imposes great challenges regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Exploring the role of blockchain technology in maritime cybersecurity, Freire et al [86] suggested its application within maritime monitoring systems to protect navigation data and ensure data integrity. Similarly, Lingtong Min et al [87] proposed secure rate-splitting multiple access (RSMA) cooperation within maritime cognitive unmanned aerial vehicle (UAV) networks to enhance data security while optimizing transmission rates.…”
Section: Data Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…Exploring the role of blockchain technology in maritime cybersecurity, Freire et al [86] suggested its application within maritime monitoring systems to protect navigation data and ensure data integrity. Similarly, Lingtong Min et al [87] proposed secure rate-splitting multiple access (RSMA) cooperation within maritime cognitive unmanned aerial vehicle (UAV) networks to enhance data security while optimizing transmission rates.…”
Section: Data Securitymentioning
confidence: 99%
“…There is a consensus on the need for comprehensive education and training programs to build sufficient cybersecurity knowledge across all levels of the industry. • Data Security: Data security has been identified as a critical area of advancement, with the research proposing various strategies to protect data within the maritime sector[60,[81][82][83][84][85][86][87][88][89][90][91][92][93][94][95]. This includes the development of technologies and processes to ensure the integrity and confidentiality of maritime data.…”
mentioning
confidence: 99%
“…Jegadeesan et al (2021) proposed AIS anonymous authentication scheme. The blockchain-based authentication and integrity schemes for AIS are proposed in (Duan et al, 2022) (Freire et al, 2022).…”
Section: Related Workmentioning
confidence: 99%
“…AIS is an open standard and due to unauthenticated and unencrypted nature make it vulnerable to threats such as spoofing, hijacking, and availability disruption (Balduzzi et al, 2014) (Hall et al, 2015) (Khandker et al, 2022b) (Tran et al, 2021). To secure AIS, several security schemes have been proposed, including anonymous authentication schemes (Goudosis and Katsikas, 2022) (Jegadeesan et al, 2021), TESLA protocol-based scheme (Sciancalepore et al, 2021) and blockchain based schemes (Duan et al, 2022) (Freire et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, IoT is being used to improve maritime safety and security. Vessel traffic management systems, piracy detection systems, and emergency response systems leveraging IoT technologies are being deployed to enhance maritime security [57,58].…”
Section: Current State Of Iot Integration In the Maritime Sectormentioning
confidence: 99%